Nonlinear dynamics of multi-omics profiles during human aging - Shen, Xiaotao; Wang, Chuchu; Zhou, Xin; Zhou, Wenyu; Hornburg, Daniel; Wu, Si; Snyder, Michael P. (Nature aging, 2024)
Aging is a complex process associated with nearly all diseases. Understanding the molecular changes underlying aging and identifying therapeutic targets for aging-related diseases are crucial for increasing healthspan. Although many studies have explored linear changes during aging, the prevalence of aging-related diseases and mortality risk accelerates after specific time points, indicating the importance of studying nonlinear molecular changes. In this study, we performed comprehensive multi-omics profiling on a longitudinal human cohort of 108 participants, aged between 25 years and 75 years. The participants resided in California, United States, and were tracked for a median period of 1.7 years, with a maximum follow-up duration of 6.8 years. The analysis revealed consistent nonlinear patterns in molecular markers of aging, with substantial dysregulation occurring at two major periods occurring at approximately 44 years and 60 years of chronological age. Distinct molecules and functional pathways associated with these periods were also identified, such as immune regulation and carbohydrate metabolism that shifted during the 60-year transition and cardiovascular disease, lipid and alcohol metabolism changes at the 40-year transition. Overall, this research demonstrates that functions and risks of aging-related diseases change nonlinearly across the human lifespan and provides insights into the molecular and biological pathways involved in these changes. Understanding the molecular changes underlying aging is important for developing biomarkers and healthy aging interventions. In this study, the authors used comprehensive multi-omics data to reveal nonlinear molecular profiles across chronological ages, highlighting two substantial variations observed around ages 40 and 60, which are linked to increased disease risks.